2017
DOI: 10.1007/s00204-017-2046-2
|View full text |Cite|
|
Sign up to set email alerts
|

Quantification of N-phenyl-2-naphthylamine by gas chromatography and isotope-dilution mass spectrometry and its percutaneous absorption ex vivo under workplace conditions

Abstract: N-Phenyl-2-naphthylamine (P2NA) is an antioxidant used to protect rubbers from flex-cracking. P2NA can be converted in vivo to 2NA, one of the most potent bladder carcinogens. Here, we report the specific and ultra-sensitive quantification of P2NA in the receptor fluid of Franz diffusion cells by gas chromatography and isotope-dilution tandem-mass spectroscopy (GC–MS/MS). The experimental conditions were optimized to minimize losses of P2NA due to surface absorption on glass, plastic, and rubber material, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
1
1
0
1
Order By: Relevance
“…For halogenated flame retardants, adherence was not a problem in the same system (Frederiksen et al, 2016). Marek et al (2017) reported that adherence of n-phenyl-2-naphtylamine (log K ow of 4.4) was highly dependent on the receptor fluid; adding 5% bovine serum albumin to the receptor fluid, as it was done in the current study, markedly reduced the adherence to the glass surfaces in the receptor chamber.…”
Section: Mass Losssupporting
confidence: 52%
“…For halogenated flame retardants, adherence was not a problem in the same system (Frederiksen et al, 2016). Marek et al (2017) reported that adherence of n-phenyl-2-naphtylamine (log K ow of 4.4) was highly dependent on the receptor fluid; adding 5% bovine serum albumin to the receptor fluid, as it was done in the current study, markedly reduced the adherence to the glass surfaces in the receptor chamber.…”
Section: Mass Losssupporting
confidence: 52%
“…N -Phenyl-β-naphthylamine (PBNA) is a widely used antioxidant in numerous industrial applications, such as the manufacture of rubber, plastic, dyes, various greases, lubricating and transformer oils, and energetic materials. In the presence of oxidative or hydrolyzing agents such as oxygen, nitrogen oxides (NO x ), and nitrous and nitric acids (HNO x ), this secondary arylamine stabilizer can effectively protect energetic materials from oxidation or hydrolysis by scavenging the free radicals (e.g., NO 2 radical) and hence reducing the acidity. ,,,, In a similar class of antioxidants (e.g., diphenylamine and triphenylamine), nitration of arylamines generally forms nitro derivatives by reacting with nitrogen oxide radicals , and can be characterized using mass spectrometry (MS) through rationalization of fragmentation . Accordingly, PBNA can also form mononitro derivatives when it undergoes similar reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Narażenie zawodowe na FNA występuje głównie przez układ oddechowy i skórę [4][5][6]. W wyniku zatrucia ostrego FNA w postaci pyłu może wystąpić kaszel, zaczerwienienie spojówek, łzawienie oczu, ból głowy, duszności, zaburzenia świadomości, utrata przytomności i zgon.…”
Section: Wstępunclassified